Exploring Economic Dynamics and Urbanization in the Context of Environmental Impact: A Study on Capital Flows, Investment Trends, and Urban Growth - Sandip Sarker (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
This study examines the complex interactions between economic growth, urbanization, and environmental sustainability in Bangladesh, with a focus on the impact of Foreign Direct Investment (FDI), urban population expansion, and domestic credit availability on CO2 emissions. Leveraging time series data from 1990 to 2021, the research employs robust econometric models, including Ordinary Least Squares (OLS) regression and Error Correction Model (ECM), to disentangle the short-term and long-term influences of these factors on environmental degradation. The findings reveal a nuanced relationship: while FDI appears to contribute to a reduction in CO2 emissions, likely due to the infusion of cleaner technologies, urbanization and increased domestic credit significantly exacerbate emissions, underscoring the environmental costs of rapid economic development. These results highlight the urgent need for policy interventions that align economic growth with environmental sustainability, particularly through the promotion of sustainable urbanization and responsible investment practices.